Some aspects of the problems of international tax law (Journal of actual problems of jurisprudence, 2018)
The article discusses some aspects of the problems and prospects of development of international tax law. Formation and development of international tax law – the basic regulatory control of tax relations at the international level has generated enormous interest in the scientific world, while at the same time has generated a lot of discussion among scientists about the nature of this phenomenon. A variety of views expressed and positions can be reduced to two basic concepts. Key words: taxes; taxation; international tax law; international tax relations.